A demonstration of dry and viscous damping of an oscillating pendulum - Zonetti, L. F C; Camargo, A. S S [UNESP]; Sartori, J.; De Sousa, D. F.; Nunes, L. A. (IOP Publishing, 1999)
Damped oscillatory motion is one of the most widely studied movements in physics courses. Despite this fact, dry damped oscillatory motion is not commonly discussed in physics textbooks. In this work, we discuss the dry and viscous dampec pendulum, in a teaching experiment that can easily be performed by physics or engineering students.